Nursing home care for people with dementia and residents' quality of life, quality of care and staff well-being: Design of the Living Arrangements for people with Dementia (LAD) - study - de Lange Jacomine; Smit Dieneke; Willemse Bernadette M; Pot Anne (BMC Geriatrics, 2011)
Abstract Background There is limited information available on how characteristics of the organization of nursing home care and especially group living home care and staff ratio contribute to care staff well being, quality of care and residents' quality of life. Furthermore, it is unknown what the consequences of the increasingly small scale organization of care are for the amount of care staff required in 2030 when there will be much more older people with dementia. Methods/Design This manuscript describes the design of the 'Living Arrangements for people with Dementia study' (LAD-study). The aim of this study is to include living arrangements from every part of this spectrum, ranging from large scale nursing homes to small group living homes. The LAD-study exists of quantitative and qualitative research. Primary outcomes of the quantitative study are wellbeing of care staff, quality of care and quality of life of residents. Furthermore, data concerning staff ratio and characteristics of the living arrangements such as group living home care characteristics are assessed. To get more in-depth insight into the barriers and facilitators in living arrangements for people with dementia to provide good care, focus groups and Dementia Care Mapping are carried out. Discussion Results of this study are important for policymakers, directors and staff of living arrangements providing nursing home care to people with dementia and essential for the development of methods to improve quality of care, residents' and staff well-being. Data collection will be repeated every two years, to generate knowledge on the results of changing policies in this field.